Analisis Wacana Kritis Norman Fairclough dalam Stand-Up Comedy Mamat Alkatiri pada Program "Somasi" - Ni Wayan Ditha Sasmitha (Politicos: Jurnal Politik Dan Pemerintahan, 2023)
This paper analyzes the text of Mamat Alkatiri's stand-up comedy in the Somasi program on the Close the Door Youtube channel. This paper uses critical discourse analysis from Norman Fairclough. Mamat delivered his disappointment with the government, especially in terms of: (1) The overlapping division of positions; (2) public officials who seem to be 'anti-criticism'; (3) A decision-making system that reaps the pros and cons. As explained by Fairclough, discourse practices and socio-cultural conditions influence the discourse that is built. Based on the results of the analysis, Mamat's discourse cannot be separated from discourse practices which include; the media organization that produces the performance, then the characteristics of Somasi's audience that are able to accept and negotiate his comedic performance. Then the socio-cultural conditions that influence Mamat's comedy text include; the presence of subpoena phenomena in Indonesia as a situational dimension, government institutions in Indonesia, especially in bureaucratic management and decision-making systems, situational dimensions that occur in Indonesia such as the presence of subpoena phenomena which indirectly put pressure (repression) on freedom of expression. Mamat's discourse is also influenced by Mamat's political culture spirit, this spirit is the same as cyberspace's opportunity to achieve a democratic system that is coveted by cyberspace audiences. Mamat's criticism implies messages for all of us to reflect again, has the current era of government provided democratic public space.